2021
DOI: 10.3389/fpsyg.2021.646572
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-Based Coping and Spirituality During the COVID-19 Pandemic: Mediating Effects on Subjective Well-Being

Abstract: The coronavirus pandemic has significantly affected the Turkish population. During the pandemic, people with high coronavirus stress are at risk of experiencing poor subjective well-being. There is no research investigating the role of meaning-based coping and spirituality in explaining the link between coronavirus stress and subjective well-being. This study examined the mediating roles of meaning-based coping and spiritual well-being in the link between coronavirus stress and subjective well-being in young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…Similarly previous studies in the literature stated that negative mental states such as depression, anxiety, fear and stress experienced by individuals in the COVID-19 pandemic also negatively affect their subjective well-being (Droit-Volet et al, 2020 ; Paredes et al, 2021 ). In addition, in previous studies, it has been concluded that the stress during the COVID-19 pandemic negatively affects the subjective well-being of individuals (Arslan & Allen, 2021 ; Arslan & Yıldırım, 2021 ; Krok et al, 2021 ). Thus, it can be stated that the finding in this study is consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly previous studies in the literature stated that negative mental states such as depression, anxiety, fear and stress experienced by individuals in the COVID-19 pandemic also negatively affect their subjective well-being (Droit-Volet et al, 2020 ; Paredes et al, 2021 ). In addition, in previous studies, it has been concluded that the stress during the COVID-19 pandemic negatively affects the subjective well-being of individuals (Arslan & Allen, 2021 ; Arslan & Yıldırım, 2021 ; Krok et al, 2021 ). Thus, it can be stated that the finding in this study is consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 97%
“…The stress experienced by students due to the COVID-19 pandemic has led to a restless and unhappy mood (Droit-Volet et al, 2020 ). In previous studies, it was concluded that the stress experienced by students during the pandemic process negatively affects their subjective well-being and life satisfaction (Arslan & Allen, 2021 ; Arslan & Yıldırım, 2021 ; Krok et al, 2021 ). Therefore, the second hypothesis is as follows: COVID-19 student stress is a negative predictor of subjective well-being (Hypothesis-2).…”
Section: Introductionmentioning
confidence: 99%
“…Two English majors’ postgraduates back-translated and revised the Chinese Coronavirus Stress scale. Researches indicate that the scale is psychometrically adequate and has good reliability [ 114 , 115 ]. In this study, the Cronbach alpha coefficient was 0.93.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing upon phenomenological elements to evaluate the emotional mechanisms of rituals (performed in a group) and practices (performed individually), recent research has generated a number of insights, especially in terms of health and well-being-in addition to other social, emotional, and cognitive dynamics-that both rituals and practices generate, which do not necessarily require a commitment to belief (Bryce Yaden 2019; Newberg 2019). A growing body of literature focuses on the role that religion plays during the pandemic, focusing on how beliefs, virtual communities, and social capital offer means to minimise social isolation and stress (Lucchetti et al 2020;Boguszewski et al 2020;Shechter et al 2020;Arslan and Yildrim 2021;Prazeres et al 2021). In Japan, where the large majority of people describe themselves as mush ūkyō, non-religious, the resilient capacity of religious institutions to enable social and emotional dynamics to overcome the pandemic-induced adverse situations affecting people's well-being has not diminished (Cavaliere 2021a).…”
Section: "Kokoro No Kea" During the Pandemic: Institutional Responsesmentioning
confidence: 99%